Yazıcıoğlu Aḥmed Bicān ve Envārü’l-‘Āşıḳin adlı eseri - Ahmed Bîcan, ?-15. yy. (Cambridge, MA Cambridge, MA)
4 cilt (1. c. v, 210, [9] sayfa ; 2. c. v, 234, [8] sayfa ; 3. c. v, 229, [8] sayfa ; 4. c. 368, [9] sayfa)